C603– versus C604– /C602– – Synthesis and Characterization of Five Salts Containing Discrete Fullerene Anions12. Issue 5 (19th February 2014) - Boeddinghaus, M. Bele; Klein, Wilhelm; Wahl, Bernhard; Jakes, Peter; Eichel, Rüdiger‐A.; Fässler, Thomas F.
Abstract Five new compounds, [Rb(18crown‐6)]3[C60] (1), [Rb(18crown‐6)]6[C60]2(C3H7NO)2(C4H8O)2 (2), [Rb(benzo18crown‐6)]6[C60]2(C2H8N2)5 (3), [Cs(benzo18crown‐6)]3C60(C2H8N2)2 (4), and [Cs3(benzo18crown‐6)5]C60(C2H8N2)(4.5+x) (5) were synthesized and characterized by single‐crystal X‐ray structure determination. All compounds contain discrete C60 anions, which are ordered in 1, 2, and 4, where direct cation‐anion contacts occur. The unit cells of 1 and 2 contain two independent fullerides, which coordinate to the rubidium atoms either of two or of four [Rb(18crown‐6)] units. Owing to the presence of differently coordinated fullerene units in compounds 1 and 2, a possible disproportionation of C603– into C602– and C604– anions is discussed. In 3 and 4 the C60 anions are coordinated by three Rb and Cs atoms, respectively. In all compounds the average charge of the anion is –3. Magnetic data reveal a doublet spin state for 3. The EPR spectra are discussed for compounds 3 and 5. The role of a dynamic Jahn‐Teller distortion is discussed, and we report the first IR spectroscopic data of fullerene trianions, which have been obtained in solution.